2015
DOI: 10.1093/jamia/ocv138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health information technology on patient outcomes: a systematic review

Abstract: Many areas of health IT application remain understudied and the majority of studies have non-significant or mixed findings. Our study suggests that larger, higher quality studies need to be conducted, particularly in the long-term care and ambulatory care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 101 publications
0
55
1
3
Order By: Relevance
“…As was noted above, concerns about whether, and to what extent, HF and usability research is contributing to ensuring safe and usable health technologies, applications, and services require further analysis [30,31]. But as Brenner et al [63] noted in their systematic review exploring links between HIT and patient outcomes, this is perhaps part of a broader problem as 'many areas of health IT application remain understudied and the majority of studies have non-significant or mixed findings'. Similarly, Guise et al [64] have identified patient safety risks associated with telecare and recommended greater use of HF and usability approaches.…”
Section: Technology Human Factors and Usability: Old And New Problemsmentioning
confidence: 99%
“…As was noted above, concerns about whether, and to what extent, HF and usability research is contributing to ensuring safe and usable health technologies, applications, and services require further analysis [30,31]. But as Brenner et al [63] noted in their systematic review exploring links between HIT and patient outcomes, this is perhaps part of a broader problem as 'many areas of health IT application remain understudied and the majority of studies have non-significant or mixed findings'. Similarly, Guise et al [64] have identified patient safety risks associated with telecare and recommended greater use of HF and usability approaches.…”
Section: Technology Human Factors and Usability: Old And New Problemsmentioning
confidence: 99%
“…Though studies predominantly report positive consequences on patient safety parameters when using HIT (e.g., reduction of adverse events), a few studies also report on negative consequences (e.g., increase in mortality due to adverse events) which could have been avoided with thorough implementation and monitoring resulting in lives saved (Han et al, 2005;Brenner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in medication safety in paediatric oncology can be achieved by using electronic medication management (EMM) systems (also known as computerized provider order entry—CPOE) with clinical decision support (CDS; Aita et al, ; Bannan & Tully, ; Brenner et al, ; Chen & Lehmann, ; Elsaid, Garguilo, & Collins, ; Maaskant et al, ; Rinke et al, ; van Rosse et al, ; Small, Barrett, & Price, ). This technology has the potential to improve safety by facilitating the scheduling of chemotherapy cycles and associated monitoring tests, calculating cumulative doses of drugs and supporting medication workflows (Allen et al, ; Elsaid et al, ; Gandhi, Tyono, Pasetka, & Trudeau, ; Hoffman, Baker, Howard, Laver, & Shenep, ).…”
Section: Introductionmentioning
confidence: 99%